1989
DOI: 10.2527/jas1989.67123495x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of a Specific mRNA in Longissimus Muscle of Steers Fed Ractopamine

Abstract: To address the hypothesis that some classes of growth promoters stimulate muscle protein synthesis in growing cattle, 23 crossbred steers were fed diets containing the phenethanolamine growth promoter ractopamine in a 140-d feeding trial. Steers received either no ractopamine, .18 or .36 mg.kg BW-1.d-1 ractopamine for 140 d or .36 or .72 mg.kg BW-1.d-1 ractopamine for 56 d. Longissimus muscle was obtained at slaughter and frozen in liquid N2. RNA was extracted by homogenization of pulverized frozen muscle in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
3

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 0 publications
1
21
1
3
Order By: Relevance
“…One unique aspect of our experiment is the investigation of gene expression at two time points relative to the administration of clenbuterol. Previous studies have focused on altered gene and/or protein expression after significant changes in muscle mass have occurred [12,13,23]. However, results of our study indicate that changes in gene expression are equally abundant at an early time point relative to the initiation of clenbuterol administration.…”
Section: Discussioncontrasting
confidence: 70%
“…One unique aspect of our experiment is the investigation of gene expression at two time points relative to the administration of clenbuterol. Previous studies have focused on altered gene and/or protein expression after significant changes in muscle mass have occurred [12,13,23]. However, results of our study indicate that changes in gene expression are equally abundant at an early time point relative to the initiation of clenbuterol administration.…”
Section: Discussioncontrasting
confidence: 70%
“…This result was comparable to data reported for trials using ractopamine from steers, when the total RNA content of 1. dorsi was not changed by treatment [37]. Other studies with rat [5], however, have suggested B-agonist-induced increases in muscle RNA, indicating the likelihood of muscle type and species variation.…”
Section: Analysis Of Bovine Rnamentioning
confidence: 77%
“…This β-AA induced muscle hypertrophy is accredited to an increased rate of muscle α-actin synthesis, as well as to the inhibitory activity of calpastatin (Smith et al, 1989;Yang and McElligott, 1989). Fat deposition in several organs can also be usually affected by β-AA supplementation.…”
Section: Discussionmentioning
confidence: 99%